2016
DOI: 10.24867/jged-2016-1-027
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of durability the evaluation of relief-dot braille images

Abstract: The paper presents a model of factors that influence on the quality of relief-dot Braille inscriptions in their intensive use by blind people. It was constructed matrix of depending and distancing by using a directed graph. It allowed establish a hierarchy between studied criteria’s of impact the on durability of relief prints. It was developed a basic structure of digital system of assessment the conformity of Braille symbols to applicable international standards and definition of operational stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…Зазначені Проведення досліджень на тактильне відчуття рельєфно-крапкових елементів шрифту Брайля є ключовим етапом визначення технологічних параметрів друку при виготовленні видань для незрячих людей, які забезпечать необхідну тактильність та читабельність. У джерелах [7,8] зазначаються позитивні результати з читабельності відбитків, виготовлених тисненням, цифровим друком з лакуванням та без. Згідно проведених досліджень виявлено, що лакування написів у виданнях зі шрифтом Брайля не є доцільним, оскільки це знижує читабельність, за рахунок відсутності тертя між контактуючими поверхнями.…”
Section: постановка проблемиunclassified
See 1 more Smart Citation
“…Зазначені Проведення досліджень на тактильне відчуття рельєфно-крапкових елементів шрифту Брайля є ключовим етапом визначення технологічних параметрів друку при виготовленні видань для незрячих людей, які забезпечать необхідну тактильність та читабельність. У джерелах [7,8] зазначаються позитивні результати з читабельності відбитків, виготовлених тисненням, цифровим друком з лакуванням та без. Згідно проведених досліджень виявлено, що лакування написів у виданнях зі шрифтом Брайля не є доцільним, оскільки це знижує читабельність, за рахунок відсутності тертя між контактуючими поверхнями.…”
Section: постановка проблемиunclassified
“…Якщо порівняти шорсткість шкіри людини та наждачний папір, використаний для проведення дослідження, можна дійти висновку, що видання надруковані струминним друком шрифтом Брайля є довговічними. Отримані результати стійкості до стирання відповідають даним щодо стійкості крапок Брайля до здирання, отриманих цифровим друком [12].…”
Section: результати проведених дослідженьunclassified
“…Certain studies, e.g. a simulation of a Braille image longevity evaluation process by developing a digital control system of the conformity of parameters of Braille symbols with the representation of a model of factors affecting the quality of Braille in their active usage by the blind [1], are known. Furthermore, the influence of a superficial topography and friction on human perception is studied, because there is a presumption that superficial geometric peculiarities play an important role in perception [2], friction coefficients are analysed, analysis or study methods are suggested, wherein different types of surfaces may be correlated with friction and tactile response [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Аналіз впливу виокремлених чинників проєктування тактильної продукції вказує на суттєвий взаємовплив між ними. Наприклад, спосіб друку впливає на щільність знаків та їхні геометричні параметри (діаметр і висоту крапки Л. Брайля), а від захисного покриття, матеріалуоснови для нанесення та матеріалу для утворення рельєфної крапки залежать різновид тактильної продукції та досвід читання [2,7,10].…”
unclassified